2021
DOI: 10.1017/jfm.2021.166
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of thermoacoustic instability by targeting the hubs of the turbulent networks in a bluff body stabilized combustor

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 72 publications
(142 reference statements)
1
15
0
Order By: Relevance
“…Murayama & Gotoda (2019) combined a phase synchronization parameter and the determinism (connection strength) of cross recurrence plots to build weighted networks, and then used them to explain how thermoacoustic oscillations can be weakened with secondary air injection. Recently, Krishnan et al (2021) constructed time-varying weighted spatial turbulent networks based on the Biot-Savart law, and showed that thermoacoustic instability can be suppressed by targeting the primary network hubs (i.e. the fluid elements with high vorticity) with steady air jets.…”
Section: Complex Network In Thermoacousticsmentioning
confidence: 99%
“…Murayama & Gotoda (2019) combined a phase synchronization parameter and the determinism (connection strength) of cross recurrence plots to build weighted networks, and then used them to explain how thermoacoustic oscillations can be weakened with secondary air injection. Recently, Krishnan et al (2021) constructed time-varying weighted spatial turbulent networks based on the Biot-Savart law, and showed that thermoacoustic instability can be suppressed by targeting the primary network hubs (i.e. the fluid elements with high vorticity) with steady air jets.…”
Section: Complex Network In Thermoacousticsmentioning
confidence: 99%
“…In this twodimensional system, flow elements at grid points (Fig. 2) are considered as nodes, and links between two nodes represent the interaction between these flow elements 45,61 . The magnitude of the velocity induced by the vorticity of a flow element at the i th grid point on another flow element at the j th grid point (V i→ j ) (Fig.…”
Section: B Construction Of Time-evolving Directed Networkmentioning
confidence: 99%
“…In recent decades, complex networks theory has emerged as one of the most powerful tools in understanding the interactions between the different units of a complex system across various disciplines [40][41][42][43][44][45] . Tsonis et al 46 first applied this theory to study climate, by considering the climate system to be represented by a grid of oscillators interacting with each other in a complex way, with each one representing climate variability of a particular location of the gridded spatiotemporal dataset.…”
Section: Introductionmentioning
confidence: 99%
“…The complex-network approach (Newman 2010;Barabási 2016) inspired by discrete mathematics has recently enabled us to clarify the nonlinear dynamics of intermediate-frequency combustion instability in several turbulent combustors (Murugesan & Sujith 2015;Okuno, Small & Gotoda 2015;Godavarthi et al 2018;Murayama et al 2018;Guan et al 2019;Kobayashi et al 2019;Krishnan et al 2019bKrishnan et al , 2021. The importance of the complex-network approach in the fields of combustion engineering and fluid physics has been shown in some recent review articles (Juniper & Sujith 2018;Sujith & Unni 2020Iacobello, Ridolfi & Scarsoglio 2021) and a book (Sujith & Pawar 2021).…”
Section: Introductionmentioning
confidence: 99%